Faktor Risiko Keluhan Subjektif Kejadian Keracunan Petani Sayur di Desa Plaosan Kabupaten Magetan - Dwi Nurcahyo; Vincentius Supriyono; Aries Prasetyo; Sujangi (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2023)
Chemicals and other materials in the form of jasad renik and viruses are used to prevent or eradicate pests that can damage plants. They are usually called pesticides. Some plants or agricultural products that stimulate plant growth kill some plants without fertiliser and prevent unwanted growth. Severe poisoning refers to low-level long-term effects or exposure to toxic substances, such as frequent spraying of pesticides during dangerous spraying times. The effects of chronic exposure do not appear immediately after the first exposure; it takes a long time for symptoms to appear. Plaosan is one of the villages and sub-districts in Magetan district where part of the population works as vegetable farmers. The population in Plaosan village is 5,678 people spread over 5 hamlets, namely Gulun, Duwet, Kauman, Sale, and Kandenan. To increase optimal agricultural yields, farmers in agricultural intensification usually use pesticides. Pesticides continue to accumulate in the body and slowly damage the tissues. People who are frequently exposed to this pesticide at low doses may suffer from symptoms of poisoning long after their initial exposure. Chronic symptoms include chronic oral inhalation poisoning and chronic skin contact. This research uses a descriptive type of research. Descriptive research is a study that describes the magnitude of the problem under study. Descriptive research is research with the main objective of making an objective picture or description of a situation. This study aims to determine the risk factors for subjective complaints of pesticide poisoning of vegetable farmers in the work area of the Plaosan Health Centre in terms of individual factors, behaviour, environment, and pesticide use. The results of this study regarding the risk factors of subjective complaints All farmers experienced complaints of severe, moderate, and mild health complaints, including headaches, dizziness, nausea, vomiting, a weak body, nervousness, trembling, blurred vision, sweating a lot, a fast heart rate, and difficulty breathing.